Effects of Artemisia annua alcohol extract on physiological and innate immunity of Nile tilapia (Oreochromis niloticus) to improve health status - Soares, Michelly Pereira [UNESP]; Cardoso, Israel Luz [UNESP]; Ishikawa, Márcia Mayumi; de Oliveira, Adriana da Silva Santos; Sartoratto, Adilson; Jonsson, Claudio Martin; de Queiroz, Sonia Claudia do Nascimento; Duarte, Marta Cristina Teixeira; Rantin, Francisco Tadeu [UNESP]; Sampaio, Fernanda Garcia (Elsevier, 2020)
Plants are a potential source of active molecules and are environmentally safer and cheaper than synthetic antibiotics. Bioactive compounds of Artemisia annua have shown pharmacological activities and are used globally as a supplement. The present study tested whether dietary supplementation with alcohol extract of the plant A. annua (ae-Aa; patent BR10201902707) improves the health status of juvenile Nile tilapia and increases resistance to diseases when fish are challenged with the bacteria Aeromonas hydrophila. The experimental design was completely randomized with four experimental groups (0.0, 0.1, 0.25, and 0.5% ae-Aa in the diets) with five repetitions (12 fish per repetition/experimental unit). We assessed serum glucose and cortisol levels in plasma, leukocyte respiratory activity, total plasma protein, serum lysozyme levels, as well as the number of circulating red blood cells and fish leukocytes at the end of the 30 days of feeding (phase I) and 24h after exposure to bacteria (phase II). The levels of lipid peroxidation, catalase activity and glutathione S-transferase of fish were also analyzed. The supplementation of 0.5% of ae-Aa was sufficient to increase the respiratory burst of leukocyte and lysozyme activity, total plasma protein, blood thrombocytes, neutrophils and monocytes after bacterial challenge (P < 0.05), and minimized stress response with decreases in plasmatic glucose and cortisol, and reduction in lipid peroxidation levels (P < 0.05). Results of the present study suggest that ae-Aa as a dietary supplement has benefits, including supplementation with 0.5% A. annua extract for 30 days to minimize the stress response and modulate innate immunity in Nile tilapia, providing fish with greater resistance and disease protection.
Keywords: Artemisia annua L; Artemisinin; Bacterial challenge; Herbal immunostimulants; Oxidative stress; Stress